Impact ionization characteristics in avalanche photodiodes - Gokul Jayaram. (2013)
Avalanche photodiodes are a classification of semiconductor devices known for their high sensitivity and high speed. They convert light to electricity using the photo-electric effect. Like normal photodiodes, absorption of incident photons generate electron-hole pairs (EHPs), which cause conductivity. Gain is produced when impact ionization results in avalanche multiplication of electrons or holes (can be electron-initiated or hole-initiated multiplication). The difference here is the reverse bias voltage applied to the device, which can be as high as 100-200 V in Silicon.